Vibration Analysis of Perforated Composite Sandwich Plate (Journal of University of Babylon for Engineering Sciences, 2018)
This paper presents a simulation study of free and forced vibration of perforated composite sandwich plates. The modal characteristics are consists of three layers, the material of the lower and upper face sheets are hard orthotropic composite material (carbon-epoxy composite) and the core layer material is soft orthotropic foam. With simply support, boundary condition at all edges has been analyzed. The natural frequency and mode shape of the panels has been obtained using finite element analysis (ANSYS 15). The effect of number of holes and perforation ratio on vibrations was investigated. The results showed that the increase in perforation ratio at certain value of  holes lead to change the frequency that occurs resonance. The results can be used to control the changes in dynamic characteristics of perforated sandwich composite plate with specified number of holes and perforation ratio. The approach can also be suitable to control the dynamic responses of such perforated composite sandwich plates.